PTH-032 Assessing the merits of sedation practice on comfort scores during gastroscopy training procedures in the uk. (17th June 2017) - Napier, DJ; Ward, ST; Brown, J; Anderson, JT; Dunckley, P
Abstract : Introduction: Oesophagogastroduodenoscopy (OGD) is invaluable in the investigation and treatment of the upper gastrointestinal tract, but may cause patient anxiety and discomfort. Many patients elect to have no sedation. For the remainder, sedation practice varies with limited data regarding the merits or risks of differing sedation practice. The 2004 NCEPOD report "Scoping our practice" 1 raised concerns about sedation practice in the UK. Sedation practice is safer now 2, but there has been limited research into minimising patient discomfort. This study compared patient comfort scores using different combinations of sedation; midazolam alone, a combination of pharyngeal anaesthesia (PA) and midazolam, or a combination of PA, midazolam and opiates. Method: Retrospective data from the Joint Advisory Group (JAG) Endoscopy Training System (JETS) database of patients having OGDs performed by trainees between September 2009 and March 2016 was analysed. Procedures carried out under general anaesthesia and in patients under 18 years of age were excluded. Procedural discomfort was scored using the Gloucester comfort scale and grouped into: significant discomfort (4 or 5) and non-significant discomfort (1, 2 or 3). A multivariate analysis was used to compare data. Data was reviewed to determine if sedation practice effected immediate complication rates. Results: 826, 593 OGDs were included in the study. 46.9% (387886) of procedures used PA alone, 23.4% (193014) PA and midazolam, 17.5% (144315) midazolam alone and 3.1% (26017) PA, midazolam and opiates. Average doses of midazolam used were 2.44 mg (PA and midazolam) compared with 2.68 mg (midazolam alone). Patients had less significant discomfort when midazolam was used in combination compared to midazolam alone; midazolam with PA (OR 0.69, 95% CI 0.67–0.72 p<0.01) and midazolam with PA and opiates (OR 0.60, 95% CI 0.55–0.65 p<0.01). There was no statistically significant difference in immediate complication rates when comparing with midazolam alone; PA and midazolam (OR 1.36, 95% CI 0.80–2.32 p=0.25) or PA, midazolam and opiates (OR 0.92, 95% CI 0.31–2.72 p 0.88) vs midazolam alone. Conclusion: This study describes a variation in sedation practice for OGDs in the UK. The use of midazolam in combination therapy is correlated with better comfort scores with no increase in immediate complications. References: . Scoping our practice. NCEPOD. London 2004, (http://www.ncepod.org.uk/2004report/) . Gavin DR, et al. The national colonoscopy audit: a nationwide assessment of the quality and safety of colonoscopy in the UK. Gut2013;62(2):242–249 Disclosure of Interest: None Declared